Sports marketing: Research on NBA marketing strategy in Chinese market - Zhang Xin (2020)
This study explores the NBA's marketing strategies in China through the influence of 4Ps on purchase intention. Using a sample of 288 valid questionnaires collected in China, multiple linear regression analyses were employed to test the hypotheses. Research shows that product quality and public relations have a positive relationship with the purchase intention. NBA's product strategy and promotion strategy have a direct impact on the purchase intention. But the price strategy and the place strategy have no influence on the purchase intention.